Levy Flight Safe Experimentation Dynamics Algorithm for Data-Based PID Tuning of Flexible Joint Robot - Ahmad, Mohd Ashraf; Mohd Rashid, Muhammad Ikram; Sulaiman, Mohd Herwan; Suid, Mohd Helmi; Mohd Tumari, Mohd Zaidi (2020 IEEE 10th Symposium on Computer Applications & Industrial Electronics (ISCAIE), 2020)
This paper proposes the data-based PID controller of flexible joint robot based on Levy Flight Safe Experimentation Dynamics (LFSED) algorithm. The LFSED algorithm is an enhanced version of SED algorithm where the random perturbation of the updated tuning variable is based on Levy Flight function. By adopting the Levy Flight term to the updated equation of SED, it is expected that a more efficient searching can be performed than the uniform distribution random numbers. The effectiveness of the LFSED algorithm is verified to tune the PID controller of flexible joint robot. In this flexible joint control problem, two PID controllers are utilized to control both rotary angle tracking and vibration of flexible joint robot. The performance of the proposed data-based PID controller is assessed in terms of trajectory tracking of angular motion, vibration reduction and statistical analysis of the predefined control objective function. The simulation results showed that the data-based PID controller based on LFSED is able to produce better control accuracy than the conventional LFSED based method.